2008
DOI: 10.1002/ijc.23543
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome in clinically stage II melanoma patients is associated with the presence of activated tumor infiltrating T‐lymphocytes and preserved MHC class I antigen expression

Abstract: In this study we investigated whether the presence of specific populations of tumor infiltrating lymphocytes (TILs) in diagnostic primary melanoma biopsies are related to outcome in clinically stage II melanoma patients. Moreover, we investigated whether the presence of TILs correlates with expression of MHC class I antigen and MHC class II antigen on tumor cells and/or tumor infiltrating antigen presenting cells. Diagnostic primary melanoma samples of 15 patients with an unfavorable outcome were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 43 publications
5
66
1
6
Order By: Relevance
“…The current study suggests that the treatment of patients with a BRAF inhibitor may increase both Th-cell and cytotoxic T-cell responses against the tumor and that this may contribute to their therapeutic effects. Previous studies have shown that increased expression of Granzyme B-expressing CD8 þ (active) and CD4 þ cells in stage II melanoma biopsies correlated with a favorable outcome (19). The results in the current study showing that an increase in the number of CD8 þ and Granzyme B þ T cells correlated with a decrease in posttreatment biopsied lesion diameter are consistent with these findings.…”
Section: Cd20supporting
confidence: 91%
“…The current study suggests that the treatment of patients with a BRAF inhibitor may increase both Th-cell and cytotoxic T-cell responses against the tumor and that this may contribute to their therapeutic effects. Previous studies have shown that increased expression of Granzyme B-expressing CD8 þ (active) and CD4 þ cells in stage II melanoma biopsies correlated with a favorable outcome (19). The results in the current study showing that an increase in the number of CD8 þ and Granzyme B þ T cells correlated with a decrease in posttreatment biopsied lesion diameter are consistent with these findings.…”
Section: Cd20supporting
confidence: 91%
“…17,18 A majority of studies have attempted to correlate numbers of tumor-infiltrating CD8 + T cells with clinical outcome, whereas none have, to our knowledge, analyzed TCR clonotypic diversity in relation to the anatomic location of T cells in FL tissues. In order to investigate whether a correlation between location (perifollicular versus intrafollicular) and the TCR diversity of CD8 + T cells exists in FL tissues, we undertook an immunohistochemical analysis of CD8 + T cells and compared it with CD8 + TCRb sequencing in these 6 FL samples.…”
Section: Correlation Between Cd8 + T-cell Clonal Diversity and Locatimentioning
confidence: 99%
“…102,104 Clinically, decreased MHC class I expression is associated with melanoma progression, therapeutic failure, and poor clinical outcome. [105][106][107] Interestingly, although suppression of MHC class I expression by melanoma stem cells may enable evasion from CD8 þ T lymphocytes of the adaptive immune response, low MHC class I expression would be predicted to increase their susceptibility to NK cells of the innate immune system, which are normally inhibited by MHC class I molecules. However, it is conceivable that melanoma stem cells may escape NK cells by altering their expression of additional surface molecules, such as NK cell ligands, which have activating or inhibitory effects on NK cells.…”
Section: How Melanoma Stem Cells May Evade and Modulate Host Immunitymentioning
confidence: 99%